What we say when we criminalise: a metanormative inquiry - Fassnidge, J. P. (Law thesis and dissertation collection, 2023)
Criminalisation has become a central topic for criminal law theorising. One idea that has drawn much scholarly attention is that criminalising a conduct involves, in some important way, the concept of wrongdoing. The conduct criminalised, it is usually said, are wrongs and this should play an important role in explaining both what is expressed through criminalising them and on how we should decide to criminalise said conduct. A recent trend in criminalisation theory has been to argue that the fact a criminalised conduct is, specifically, morally wrongful should be relevant to criminalisation in the way just described. If that were to be the case, then it becomes particularly important to have clarity as to what we mean by a conduct being morally wrongful and how we can go about determining that that is the case. In parallel, there have been lively debates in philosophy about the nature and characteristics of morality, embodied primarily in the discipline of metaethics (sometimes also called meta-normativity). In these debates, accounts of what it means to say or to believe that something is morally wrongful vary greatly, to the point where holding different metaethical views entails completely different kinds of understandings of what it means for something to be ‘morally wrong’. Being unclear about these differences risks talking past each other when trying to discuss moral wrongness. To date, these differences in metaethical stances have not been explored or taken up by criminalisation theorists, which leaves an important theoretical gap in criminalisation literature and theorising: if we mean different things by ‘moral wrongness’, we are not able to fully analyse and evaluate proposed theoretical frameworks for understanding criminalisation that use moral wrongness as a key concept in the framework. This thesis seeks to investigate the connections between criminalisation and metaethics, under the assumption that the concept of wrongfulness is indeed to play any role in criminalisation, and show that criminalisation theorising would benefit from discussing these connections and from incorporating metaethical investigations into our normative theorising of criminalisation. I argue that there are important differences between proposing that we are expressing, through criminalisation, that the criminalised conduct is morally wrongful, and proposing that we should use the supposed moral wrongfulness of the conduct in question as a deciding factor regarding its criminalisation. I explore these differences by making a distinction between different stages at which moral wrongfulness could potentially appear in the criminalisation process and its theorising. One way to approach criminalisation is to look at it as a process by which we use the law to make it the case that a conduct is, from now on, considered a criminal offence. In doing so, I argue that it is useful to view this action as a form of speech, by which we say something, through the act of criminalisation, about the conduct being criminalised - I call this the declarative stage. Another approach to theorising about criminalisation has been to view it as a decision-making process, by which a potential decision-maker is faced with the question of whether they should criminalise a conduct or not. In doing so, theorists can provide these decision-makers with normative frameworks under which they, supposedly, should make this decision and base it on sound normative principles - I call this the deliberative stage. Once this distinction is made, I argue that both stages at which wrongfulness might be used in understanding criminalisation generate different possible meta-ethical questions about the nature and characteristics of that wrongfulness. I call these the conceptual, the ontological and the epistemic questions, which I explore in detail in chapter 2. The conceptual question asks about what is distinctive about the fact that the wrongfulness being invoked is specifically of a ‘moral’ kind. The ontological question asks about the characteristics of the existence (or lack thereof) of moral facts, properties and reasons. The epistemic question asks about access to, and the existence of, moral knowledge. By discussing different possible answers to these questions, this thesis intends to show that using ‘wrongfulness’ without giving a meta-ethical context for its use leaves many open questions that, if left unresolved, can entail very different understandings of what happens, and what should happen, when a conduct is criminalised. Once the metaethical questions relevant to this thesis have been established, I then propose a framework for understanding each stage at which wrongfulness may appear within criminalisation, starting with the declarative stage in chapter 3. In it, I present an original framework of criminalisation as a speech-act, where different normative facts are included into the act of criminalisation. I argue that if wrongfulness is to play any role in what is conceptually involved in the act of criminalisation, then it must be as a kind of implicit assertion of the fact that the conduct being criminalised is morally wrongful. I then argue that, since this is an implicit assertion, a hearer of the speech-act needs to have enough contextual information in order to reasonably infer that the wrongness being asserted implicitly is of a moral kind. One way to argue that this is the case is that the declared normative facts included in the speech-act - an obligation not to do the conduct, a liability to punishment if one does, and a responsibility to answer for one’s doing of the criminalised conduct - can be understood as the appropriate response to moral wrongdoing. I then show how this view requires making important metaethical assumptions about moral wrongness, and I show these assumptions, and potential difficulties with them, through asking the conceptual, ontological and epistemic questions posed in chapter 2. In chapter 4, I then move on to the deliberative stage, where I look at different normative theories of criminalisation which use the concept of wrongfulness in some important way. I explore some of the leading works of recent criminalisation theorists and how they use moral wrongfulness as a positive reason in favour of criminalising a conduct and/or as a negative constraint against criminalising non-wrongful conduct. I then apply the meta-ethical questions I have identified in order to construct potential answers that could represent the metaethical assumptions these theorists are making in their theorising. Particularly, different assumptions about the conceptual delimitation of moral wrongfulness, the ontological nature of the property ‘moral wrongfulness’ and the epistemic expectations one might impose on potential decision-makers as to how to gain epistemic access to moral wrongfulness can shift how some of those criminalisation theories work. I argue that in order to adequately use moral wrongfulness as a potential guiding principle (in its positive or negative form) for how we should decide whether to criminalise conduct, a theorist would benefit from providing a story as to what using that wrongfulness entails in meta-ethical terms, as this would avoid leaving theoretical gaps and would give clearer tools for potential decision-makers trying to apply these theories at the deliberative stage. Not doing so, in turn, can lead decision-makers to fill in the gaps and reach very different results, using the same deliberation process proposed by a theorist, because of making different metaethical assumptions. Chapter 5 looks at a slightly different kind of theory, which presents itself as an alternative to more orthodox ‘legal moralist’ theories and is critical of the use of moral wrongfulness as part of criminalisation theories, that has been dubbed by some the ‘political turn’ theories of criminalisation. These theories propose, in a nutshell, that instead of using ‘moral’ wrongness in our theorising of criminalisation, we should instead focus on a ‘political’ kind of normative fact in guiding decisions about criminalisation and criminal punishment. After analysing some examples of this kind of theorising, I show that they are dependent on important metaethical assumptions, specifically that moral facts and political facts are plausibly distinct. Then, I argue that there are two senses in which a political turn theorist can propose this distinction as intelligible: either as a subset of morality which is deemed ‘political’ (political moralist), or as a distinct normative domain, which is not the same as the moral (political realist). Both of these options, however, require the political turn theorist to choose between bullets to bite: either accept that political turn theories are less of an alternative to legal moralism, and theories that use moral wrongfulness, as they might have thought, or accept that they will need to commit to full-blooded politi...